The Effect Of Surface Property Towards Bacterial Biofilm Formation - Azman, Nur Iylia Ayuni (Universiti Sains Malaysia, 2022)
The commercial PVC-DEHP blood bag has several drawbacks which make SEBS/PP film as an alternative polymer to replace it. For example, platelets aggregation and blood clotting occurred due to the leaching of DEHP plasticizer into the blood, thus making the whole blood bags have a short 42-day shelf life due to the danger of bacterial infection. Therefore, the purpose of this research is to investigate the surface properties of SEBS/PP film as an alternative polymer to substitute the current PVC blood bags and how it affects the formation of bacterial biofilm. Firstly, the SEBS/PP film was produced by using blown film molding and undergo several characterizations such as Fourier Transform Infrared (FTIR) Spectroscopy, Scanning Electron Microscopy (SEM), Water Contact Analysis and Atomic Force Microscopy (AFM). Then, antibacterial properties study was carried out by following the CLSI MO2- A11 guideline and followed by bacterial biofilm formation assessment. Two strains of bacteria were obtained from American Type Culture Collection (ATCC); E. coli ATCC 22922 and S. aureus ATCC 25923 and cultured overnight. Moreover, the bioactivity of SEBS/PP is investigated by using Simulated Body Fluid (SBF). SEBS/PP film showed to have the surface properties that can result in reduction of bacterial adherence as it consists of a higher surface contact angle then PVC-DEHP film. SEBS/PP’s surface is also able to slightly reduce the bacteria adhesion when in contact with bacteria with different wettability properties.